201k views
2 votes
Patel is solving 8x2 + 16x + 3 = 0. Which steps could he use to solve the quadratic equation? Select three options.

8(x2 + 2x + 1) = –3 + 8
x = –1 Plus or minus StartRoot StartFraction 5 Over 8 EndFraction EndRoot
x = –1 Plus or minus StartRoot StartFraction 4 Over 8 EndFraction EndRoot
8(x2 + 2x + 1) = 3 + 1
8(x2 + 2x) = –3

User Sangarllo
by
4.6k points

2 Answers

1 vote

Answer:

1

2

5

Explanation:

User Ram Vennam
by
5.2k points
0 votes

Answer:

8(x2 + 2x) = –3

8(x2 + 2x + 1) = –3 + 8

x = –1 Plus or minus StartRoot StartFraction 5 Over 8 EndFraction EndRoot

Explanation:

Solving Quadratic Equations

Sometimes it's preferred to solve quadratic equations without the use of the known quadratic formula solver. One of the most-used methods consists of completing squares and solving for x.

We have the equation


\displaystyle 8x^2+16x+3=0

We separate variables from constants


\displaystyle 8x^2+16x=-3

Taking the common factor 8


\displaystyle 8(x^2+2x)=-3

Completing squares in the brackets and balancing the equation in the right side


\displaystyle 8(x^2+2x+1)=-3+8

Factoring the perfect square


\displaystyle 8(x+1)^2=5

Isolating x


\displaystyle (x+1)^2=(5)/(8)


\displaystyle (x+1)=\pm \sqrt{(5)/(8)}


\displaystyle x=-1\pm \sqrt{(5)/(8)}

We can clearly see the steps used to solve the quadratic equation are (in order and written like in the question)

8(x2 + 2x) = –3

8(x2 + 2x + 1) = –3 + 8

x = –1 Plus or minus StartRoot StartFraction 5 Over 8 EndFraction EndRoot

User Mojtaba Arezoomand
by
5.2k points